116k views
4 votes

\frac{(3 {a}^(2) )(4 {b}^(3) )}{16( {a}^(2)b) {}^(2) } =Simplify this fraction

\frac{(3 {a}^(2) )(4 {b}^(3) )}{16( {a}^(2)b) {}^(2) } =Simplify this fraction-example-1

1 Answer

1 vote

We can multiply the terms of top, then we have


((3a^2)(4b^3))/(16(a^2b)^2)=(12a^2b^3)/(16(a^2b)^2)

now, in the denominator, we have


16(a^2b)^2=16a^(2\cdot2)b^2=16a^4b^2

then, we obtain


((3a^2)(4b^3))/(16(a^2b)^2)=\frac{12a^2b^3}{16a^4b^2^{}}

Now, we can see that


(12)/(16)=(4\cdot3)/(4\cdot4)=(3)/(4)

and


(a^2)/(a^4)=(a^2)/(a^2\cdot a^2)=(1)/(a^2)

and also


(b^3)/(b^2)=(b^2\cdot b)/(b^2)=b

by combaning these results, the answer is


((3a^2)(4b^3))/(16(a^2b)^2)=\frac{3b}{4a^2^{}}

User Supercat
by
4.0k points